Um livro mu(n)do: técnica, intermidialidade e cosmopolitismo em Pathé-Baby, de António de Alcântara Machado - Zamberlan, Lucas da Cunha (2017)
This thesis aims to assess the relevance of the narrative Pathé-Baby, by the writer António de Alcântara Machado, as an inter-mediatic cultural product in the process of aesthetic affirmation of Brazilian Modernism. In this way, it is inscribed in the parameters of comparative studies, fundamentally linked to the universe of relations among literature, other arts and media. Besides the main goal, the research also aims: a) to understand the work of Alcântara Machado as a verbal work circumscribed in a period of transition between two aesthetics, Art Nouveau and Art Deco, verifying the intense exchange of Pathé-Baby with its complex structure and cosmopolitan content, and these sensibilities, which are present in arts in general, applied arts, fashion and behavior; b) map the technical innovations and operational improvements of the period, found in cinematography, phonography, telegraphy, typography, radio, photography, and other communication vehicles, understanding how the research corpus aesthetically mimics such procedures; c) to investigate, in the facsimile edition of Pathé-Baby the aesthetic appropriation of visual resources in the comparative dialogue of literature with other arts and media, such as cinema, painting, illustration and advertising poster; d) to understand the vision of a Brazilian modernist writer/journalist motivated by the innovations of the cinematographic capture of reality, realizing how his internationalization process influences his relationship with the native land. In order to achieve these goals, a methodological course was followed firstly in the thorough investigation of the artistic potential that the text of Alcântara Machado elicits in order to turn to the critical fortune, especially Rajewsky, Clüver, Louvel, Hoek, Süssekind, Eco, Hobsbawm, Sevcenko and Rosenfeld. Thereby, the thesis is divided into two chapters. The first chapter focuses on promoting an extensive and fertile dialogue between the book and the historical, social, cultural and artistic context of Brazil and the world of the late nineteenth and early twentieth century, highlighting aesthetic and technical elements that contributed decisively for the elaboration of the narrative. The second chapter is concerned with investigating the deep and complex inter-media relations that the text presents, emphasizing the approximation of the author's literature, especially with the cinema, as well as painting, illustration and advertising poster. From these elements, we can see the importance that Pathé-Baby has as an inter-mediatic cultural product in the context of Brazilian literature, as well as in the modernist art itself of the 1920’s.